THE INFLUENCE OF SHARIA HOTEL LITERACY, SERVICE AND PROMOTION ON CONSUMERS' DECISIONS TO USE SHARIA HOTEL SERVICES IN MEDAN CITY, WITH RELIGIOSITY AS AN INTERVENING VARIABLE - Pradesyah, Riyan; Bara, AL (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to see the direct and indirect influence between the variables of sharia hotel literacy, service and promotion on consumers' decisions to use sharia hotel services in the city of Medan, with riligiusity as an intervening variable. This research was conducted in medan city, using Smart PLS analysis tool. As for the results obtained, itdoes nothave a significant influence on the decision of consumers to use sharia hotel services. This is evidenced by the t-static results obtained, namely 0.4171.96 and the pvalues results of 0.6670.05. Itdoes nothave a significant effect on the decision of consumers to use sharia hotel services. This is evidenced by the t-static results obtained, namely 0.6711.96 and the pvalues results of 0.5020.05. There is a significant influence of promotion on consumers' decisions to use sharia hotel services. This is evidenced by the t-static results obtained, namely 3.4161.96 and the p values result of 0.00 10.05. There is a significant influence of religiosity on consumers' decisions to use sharia hotel services. This is evidenced by the t-static results obtained, namely 3. 2581.96 and pvalues result 0.0010.05. Sharia hotel literacy has an indirect influence on consumers' decisions to use sharia hotel services, with religiosity as an intervening variable. Services do not have an indirect influence on consumers' decisions to use sharia hotel services, with religiosity as an intervening variable. Service does not have an indirect influence on consumers' decisions to use sharia hotel services, with religiosity as an intervening variable